Kepastian Hukum Tentang Legalitas Perkawinan dan Pencatatan Bagi Umat Beda Agama Di Indonesia - Eko Purwanto; Herowati Poesoko; Moh Zeinudin (JURNAL HUKUM PELITA, 2025)
Regulations regarding interfaith marriage and registration in Indonesia have developed dynamically over time. It was found that there were court decisions rejecting interfaith marriages and their registration, but it was also found that there were court decisions granting permission. This is considered to cause legal uncertainty, because inter-religious marriages still continue to occur, while Law Number 1 of 1974 concerning Marriage and its amendments do not yet strictly and clearly regulate inter-religious marriages. This research focuses on examining the meaning of interfaith marriage and its registration over time in Indonesia as well as the direction of legal reconstruction in the future. This research is normative legal research that uses a statutory approach, a historical approach and a case approach. The legal hermeneutics research method is used to analyze the collected legal material. The research results found that the meaning of interfaith marriage and its registration experienced dynamics in its historical development in Indonesia from time to time, giving rise to legal uncertainty. Interfaith marriages and their registration can be given legal certainty by using a Court Decision or carried out abroad (in a country that permits interfaith marriages) and then reporting the registration administratively to the Civil Registry Office or Dukcapil Office to obtain legal certainty based on the provisions of the Marriage Law, Regulations Government Number 9 of 1975 concerning Implementation of UUP, and Law Number 23 of 2006 concerning Population Administration, as amended by Law Number 24 of 2013